Equity market: impact of macroeconomics variables on the stock market returns in Malaysia / Syahida Syafiqah Suhaimi - Suhaimi, Syahida Syafiqah (2021)
The researcher aims to answer the issue arise which is macroeconomic variables influence the stock market return. Therefore, the purpose of this research is to examine how the rnacroeconomic variable such as interest rate, exchange rate and inflation rate will impact the stock market return. Kuala Lumpur Composite Index (KLCI) being put as an indicator to the performance of the stock market return and Malaysia's economy. This span Of period starts from 1990 until 2020, a period of 30 years. Specifically, this study is to investigate how the stock market returns reacts towards the changing figure of this macroeconomic variables. The researcher wants to determine whether the independent variables have significant or insignificant relationship with the stock market return. The dependent variable used in this study is Kuala Lumpur Composite Index and the independent variable are interest rate, exchange rate and inflation rate. Thus, the researcher uses the econometric method which is Ordinary Least Square to test the collected data, specifically it is a multiple linear regression. The obtained data will be arranged similarly to the time series data before we regress the data in the EView. The finding of this research is only money supply (M3) is significant while the other two variables are not significant. This can be supported by the recommendation given such as using another alternate independent variable such as Industrial Production, short term interest rate and crude oil price. To conclude, the stock market return is influenced positively by interest rate thus negatively related to the exchange and inflation rate.